AB1173 RHEUMATOLOGIST CARE IS ASSOCIATED WITH FEWER EMERGENCY ROOM VISITS BY PERSONS WITH GOUT. (2nd June 2020) - Schlesinger, N.; Edwards, N. L.; Clark, S.; Lipsky, P.
Abstract : Background: Gout is one of the most common inflammatory arthropathies. By searching a large administrative data base (Symphony Integrated Dataverse), we found that persons with acute gout see a rheumatologist infrequently, whereas less than 50% of advanced gout patients are seen by a rheumatologist. Notably, however, gout patients seen by rheumatologists have more frequent urate measurements and are prescribed urate lowering therapy more frequently. This study sought to determine whether involvement of a rheumatologist in gout care had a positive impact on health outcomes Objectives: To determine whether involvement of a rheumatologist had a positive impact on health outcomes of patients with gout. Methods: We carried out a retrospective analysis to identify persons with gout over an approximately 3-year period from October 2015 to December 2018. This study used data from the Truven Marketscan ® database, an administrative database covering over 190 million patients across the United States and based on fully adjudicated and paid insurance claims. Patients were identified as having gout if they were >18 years of age and had at least two medical claims for the diagnosis of gout on different days, separated by at least 3 months. Patients with acute gout were identified by ICD-10 code M10.*, chronic nontophaceous gout (M1A.***0), tophaceous gout (M1A.***1) and uncontrolled gout (M10.*, M1A.*), the latter manifested by three gout codes (any) in the primary diagnosis position and three urate measurements within the same calendar year. Particular attention was placed on Emergency Room (ER) visits by individuals in each category and by individuals who had been evaluated by a rheumatologist. Results: We identified 284, 877 gout patients. The median age was 59.2 years and 79.0% were male. Of the 230, 998 persons coded as acute gout, 10.7% were seen by a rheumatologist, whereas 26.9% of the 32, 942 coded as chronic nontophaceous gout, 47.2% of the 7, 723 coded as tophaceous gout and 43.6% of the13, 514 coded as uncontrolled gout were seen by a rheumatologist. In each gout category, the frequency of ER visits was significantly reduced in persons who had been seen by a rheumatologist (Table 1 ). In acute gout, the frequencies of ER visits in those with and without rheumatologist care were 5.6% vs 6.6% (p<0.001), respectively. In chronic nontophaceous gout it was 5.5% vs 6.7% (p=0.001); in tophaceous gout it was 10.3% vs 14.7% (p<0.001); and in uncontrolled gout it was 12.8% vs 19.0%, respectively. If the frequencies of rheumatologist-associated gout patient ER visits were applied to all gout subjects, there would have been 3, 088 less ER visits in this cohort of gout patients. Conclusion: There appears to be a positive impact of rheumatologist involvement in the care of gout patients, manifested by a significant decrease in the frequency of ER visits. Considering the inconvenience and cost of ER visits, rheumatologist care may have a significant impact on the well-being of gout patients and on the overall cost of their care. Disclosure of Interests: Naomi Schlesinger Grant/research support from: Pfizer, Amgen, Consultant of: Novartis, Horizon Therapeutics, Selecta Biosciences, Olatec, IFM Therapeutics, Mallinckrodt Pharmaceuticals, N. Lawrence Edwards Consultant of: Horizon Therapeutics, Takeda Pharmaceuticals US, Aclaris Therapeutics, Atom Biosciences, Sanders Clark: None declared, Peter Lipsky Consultant of: Horizon Therapeutics